Library interior layout and design : proceedings of the seminar, held in Frederiksdal, Denmark, June 16-20, 1980 - Fuhlrott, Rolf.; Dewe, Michael (München : New York : Saur, 1982)
The paper concerned itself with University, National and Public Library Buildings respectively.
Includes bibliographical references
kjo 16/01/2019
Loan
Keywords: Libraries; Library architecture